Clausal embedding under TO in Japanese as speech acts - Goodhue, Daniel; Shimoyama, Junko (Proceedings of the Amsterdam Colloquium, 2022)
We identify several puzzles, some novel, that are posed by clausal embedding under the Japanese complementizer TO. To resolve these puzzles, we present a unified syntax and semantics for to and clausal embedding under it. Syntactically, we claim that to-clauses are adjuncts. Interpretationally, we claim that to embeds speech acts.